Fitopedologia de disjunções florestais (ilhas de mata) em uma área de savana do município de Boa Vista, Roraima - Santos, Naiara Marta Conceição dos (2010)
This study aimed at understanding the phytopedological patterns that happen in the forest formations (forest islands) of a savannah in area of Boa Vista, Roraima. For in such a way, four forest islands located in the savannah areas of the center-east of Roraima had been sampled. (Projeto de Assentamento Nova Amazônia I). In each island five trenches for classification of the soil had been established, being a central office to island and more four following the cardinal points (east, west, north, south), 100m one of the others. Each one of these trenches four linear transectos had been established (4m x 20m) in the same way, they had been following the four cardinal directions, characterizing a Cluster (group) of transectos. Each one of these 3 transectos was far 3m of the center of trenches to prevent overlapping of measures. Each trench possessed a depth of 200cm as modal (central trench) and the others (cardinal points), with 40cm. In these trenches had been collected deformed and formed samples in the depths of 0 - 10cm, 10 - 20cm and of 20 - 40cm. The deformed samples had been used for study of density of soil, while the deformed samples, for physical and chemical analyses. A vegetation sampling for all tree individuals was established with DAP (diameter to the height of the chest) ≥ 10cm in the transectos established from trenches. Besides the DAP, each inventoried individual had its total height esteemed (m), being that all had been the target of a phytosociological analysis, for trench and island. The results had indicated that the main kind of the sampled islands had been the Latossolos (12 trenches and 4 islands), followed of Plintossolo (6 trenches and 2 islands) and Yellow red Latossolo (2 trenches and 1 islands). The tree species of bigger general representation had been Abarema floribunda (Benth.) Barney and J.W (Mimosaceae); Pouteria petiolata T.D. Penn (Sapotaceae) and Pouteria macrophilla (Lam.) Eyma (Sapotaceae), representing the biggest of the index of value of importance (IVI) of all the survey. The phytopedology standard commanded by the generic analysis (species x physical and chemical characteristics of the soil) indicated that the Tabebuia incana A. H. Gentry, Tabebuia serratifolia (Vahl) Nichols and Sorocea cf. guilleminiana Gaudich is exclusive of Latossolo, where it has predominance of high toxic aluminum concentrations and high concentrations of organic Substance, Potassium and Magnesium, both associate the high acidity (pH). On the other hand, species as Protium aracouchini (Aubl.) March and Pouteria petiolata T.D. Penn are only in typologies with better soil fertility, in special with bigger concentrations of organic substance, magnesium, clay and low toxicity of Al. The results had pointed that the studied islands of bush can possess more than one type of soil, determining differences composition of vegetation and, therefore, defining different phytopedological units. These findings are of extreme importance for decision taking that incorporates action of conservation of the soil and use of the natural resources in the forest derivatived of the savannah areas of Roraima.